Effect of varying energy density on feed intake, digestibility of nutrients and fermentation pattern in Swamp buffaloes fed on rice straw and concentrate based diet - CHANTHAKHOUN, V; WANAPAT, M; BERG, JAN (The Indian Journal of Animal Sciences, 2012)
The aim of this study was to investigate the effect of energy (TDN) level for optimum to improve nutrients, feed intake and feed digestibility in swamp buffaloes (Bubalus bubalis) fed on rice-straw-based-diet. Four, rumen-fistulated swamp buffalo bulls (4-year old) with 401±4 kg live weight were randomly assigned to receive 4 dietary treatments according to a 4×4 Latin square design. Four levels of energy (74, 76.1, 80.6 and 84.3% TDN), 12.1% CP in concentrate mixtures were fed to buffaloes with rice-straw as a roughage. The results revealed that voluntary dry matter feed intake and nutrient digestibility were altered among energy levels of the concentrate supplements. The level of TDN in the supplements had influenced on rumen pH, but not ammonia-nitrogen, blood-urea nitrogen and rumen temperature. Rumen concentrations of propionate (C3) and butyrate (C4) were significantly different between the 76.1 to 80.6 and 76.1 to 84.3%TDN, respectively, while total volatile fatty acids (VFAs), acetate and C2: C3 ratio was not altered. However, digestibilities of OM improved with concentrate containing 76.1 and 80.6% TDN, while CP improvement was higher at 76.1%TDN. Moreover, nitrogen urinary and purine derivatives (PD) excretion were significantly different between the 76.1 and 76.1 to 80.6%TDN, respectively, while PD absorption and efficiency of microbial N synthesis showed significant improvements by the use of 76.1%TDN. Based on this result, the TDN % of concentrate response at 76.1–80.6% should be recommended, when used with rice straw in buffalo.